A reproducible gold SERS substrate assisted by silver nanoparticles without using extra aggregation agents. Issue 63 (17th June 2016) - Liu, Yuping; Lu, Zhiwei; Lin, Xiang; Zhu, Hongbin; Hasi, Wuliji; Zhang, Meiling; Zhao, Xiaorong; Lou, Xiutao
Abstract : A novel and very simple silver-assisted gold SERS substrate with very excellent reproducibility and high enhancement is achieved, and the utilization of extra aggregation agents is eliminated in the colloids substrate. Abstract : Because of excellent molecular specificity, great success in chemical detection using surface-enhanced Raman scattering (SERS) has been achieved. However, the preparation of a simple and reproducible SERS substrate with good enhancement performance is still a challenge. Here we found that a silver-assisted gold SERS substrate can achieve very excellent reproducibility and high enhancement. Owing to the combined utilization of Au NPs and Ag NPs, the substrate can achieve high enhancement without using extra aggregation agents. Because hot-spots are created only by analyte molecules themselves, the adsorption of analytes on the surface of nanoparticles generating hot-spots is more stable and uniform. For colloids substrate, some problems such as random adsorption, large conglomeration are avoided. Thus the excellent reproducibility can be obtained. Besides, interference between analyte molecule and aggregation agent may occur. Thus, elimination of extra aggregation agents is desirable. The relative standard deviation of <3.7% and the enhancement factor of ∼1.5 × 10 7 are reached. The preparation of the substrate is achieved only by mixing Au colloids with Ag colloids at a certain volume ratio. By SERS measurement of Rhodamine 6G, the performance of the silver-assisted gold SERS substrate is demonstrated.